Effect of Foliar application of humic acid on growth and flowering in Freesia hybrida - Al-Turfi, Doaa Merzah Mustafa; Mashkoor, Sulaiman Abdulhussain (Journal of Kerbala for Agricultural Sciences, 2022)
The experiment was carried out in the nursery of the University of Kufa during 2022-2021 to study the response of the freesia plant to treatment with humic acid in growth and flowering; the corms were planted in pots containing an agricultural medium consisting of river sand and peat-moss at a ratio of 1:3. The experiment included the effect of the spraying of humic acid in four concentrations (0, 2, 4 and 6 ml. L-1) and with three sprays; the first spray in the stage of true leaves on 12/92021, the second was 14 days after the first spray was carried out on 12/23/2021 and the third spray was on 5/1/2022 sequentially. The experiment was applied using the Randomized Complete Block Design (R.C.B.D) at the probability level (0.05). The results showed the humic acid at a concentration of 6 ml. L-1 achieved a significant increase in the shoot dry weight, the stem inflorescence length, the flower number per inflorescence, the flowering age, the flower diameter, the chlorophyll, carbohydrates, nitrogen percentage and potassium, either at concentrations of 4 and 6 ml. L-1 achieved a significant increase in inflorescences number, flowering date, beginning date of flowering start, and increased the phosphorous percentage. At the same time, the control treatment (spraying with distilled water) gave the lowest average in all studied traits.